2009
DOI: 10.1111/j.1525-1594.2009.00739.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlations Between Spiritual Beliefs and Health‐Related Quality of Life of Chronic Hemodialysis Patients in Taiwan

Abstract: This study evaluated the correlations between spiritual beliefs and health-related quality of life (HRQOL) of hemodialysis (HD) patients in Taiwan. Participants had to complete two questionnaires: the 36-item Short Form Health Survey Questionnaire and the Royal Free Interview for Spiritual and Religious Beliefs. They were then divided into three groups according to their strength of spiritual beliefs-having no, weak, or strong beliefs. Demographic, clinical, and laboratory data among groups were compared. Corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 10 publications
1
25
0
1
Order By: Relevance
“…There were no studies identified from the UK to examine the relationship between spirituality and religion and the QOL/HRQOL of patients with ESRD. Sample sizes ranged from as low as 53 (Patel et al, 2002) to as high as 633 (Kao et al, 2009). Six of the studies specifically indicated the use of a cross-sectional design, whereas five studies did not specify a specific design although they seemed cross-sectional in nature.…”
Section: Spirituality and Quality Of Lifementioning
confidence: 99%
See 4 more Smart Citations
“…There were no studies identified from the UK to examine the relationship between spirituality and religion and the QOL/HRQOL of patients with ESRD. Sample sizes ranged from as low as 53 (Patel et al, 2002) to as high as 633 (Kao et al, 2009). Six of the studies specifically indicated the use of a cross-sectional design, whereas five studies did not specify a specific design although they seemed cross-sectional in nature.…”
Section: Spirituality and Quality Of Lifementioning
confidence: 99%
“…The sample size in the quantitative studies varied from as low as 51 participants (Song and Hanson, 2009) to as high as 633 participants (Kao et al, 2009). Four studies had ≤100 participants (51-74 participants), seven studies had a sample size ranging from 100 ≤ 200 and five studies had a sample size of ≥ 200 participants (200-633).…”
Section: Sample Size and Studied Populationmentioning
confidence: 99%
See 3 more Smart Citations